(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Electron irradiation technique was employed to induce atomic-scale defects in the walls of multi-walled carbon nanotubes (MWCNTs) using electron beam of energy 120 keV and dose of 2.16 x 1017 electrons cm-2s-1. Structural transformations of the tubes attributable to irradiation exposure were monitored by high-resolution transmission electron microscope (HRTEM) and recorded by the connected CCD camera. It was observed that only five seconds (5s) of irradiation could shrink MWCNTs of diameter 15 nm having 11 graphitic layers towards the interior hole up to 2.2 nm and bend the tube. Irradiation incorporated vacancies and the topological defects generated on the tube walls were responsible for it. It was found that the electron irradiation could destroy such MWCNTs within 9 minutes. It was speculated that irradiation induced vacancies and their adjacent dangling bonds (DBs), the pentagon and octagon rings originated from the transformations of vacancies are highly influential to enhance the hydrogen storage in MWCNTs. From the time dependent HRTEM observations, it was found out that electron irradiation period less than 4 minutes is the optimum exposure time to achieve benefit of hydrogen storage in the MWCNTs as used in the present investigation. Electron irradiation induced defects could be used to enhance hydrogen storage in MWCNTs for future applications. Keywords: Carbon nanotube; Electron irradiation; Defect; Vacancy; Hydrogen storage DOI: 10.3329/bjsir.v45i4.7378 Bangladesh J. Sci. Ind. Res. 45(4), 337-344, 2010